Search for a Diffuse Neutrino Emission in the Southern Sky with the Antares Telescope - Fusco, Luigi Antonio <1988> (Alma Mater Studiorum - Università di Bologna, 2016)
Compelling evidence of the existence of cosmic neutrinos has been reported by the IceCube collaboration. Some features of this signal could be explained by a Northern/Southern sky asymmetry of the flux. This possible asymmetry would be related to the presence of the bulk our Galaxy in the Southern sky.